Natural Bioactive Compounds from Fungi as Potential Candidates for Protease Inhibitors and Immunomodulators to Apply for Coronaviruses - Suwannarach, Nakarin; Kumla, Jaturong; Sujarit, Kanaporn; Pattananandecha, Thanawat; Saenjum, Chalermpong; Lumyong, Saisamorn (Molecules (Basel, Switzerland), 2020)
The inhibition of viral protease is an important target in antiviral drug discovery and development. To date, protease inhibitor drugs, especially HIV-1 protease inhibitors, have been available for human clinical use in the treatment of coronaviruses. However, these drugs can have adverse side effects and they can become ineffective due to eventual drug resistance. Thus, the search for natural bioactive compounds that were obtained from bio-resources that exert inhibitory capabilities against HIV-1 protease activity is of great interest. Fungi are a source of natural bioactive compounds that offer therapeutic potential in the prevention of viral diseases and for the improvement of human immunomodulation. Here, we made a brief review of the current findings on fungi as producers of protease inhibitors and studies on the relevant candidate fungal bioactive compounds that can offer immunomodulatory activities as potential therapeutic agents of coronaviruses in the future.